2021
DOI: 10.1038/s41567-021-01427-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for equilibrium exciton condensation in monolayer WTe2

Abstract: We present evidence that the two-dimensional bulk of monolayer WTe2 contains electrons and holes bound by Coulomb attraction—excitons—that spontaneously form in thermal equilibrium. On cooling from room temperature to 100 K, the conductivity develops a V-shaped dependence on electrostatic doping, while the chemical potential develops a step at the neutral point. These features are much sharper than is possible in an independent-electron picture, but they can be accounted for if electrons and holes interact str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 46 publications
(71 reference statements)
3
54
0
1
Order By: Relevance
“…We hope these issues can be overcome in actual experiments, or, in other way, the method we proposed may inspire the discovery of more suitable materials for EI. Recently, references [16,17] proved that WTe 2 went through an EI transition linked to indirect exciton at around 100 K, in alignment with our expectation.…”
Section: Resultssupporting
confidence: 89%
“…We hope these issues can be overcome in actual experiments, or, in other way, the method we proposed may inspire the discovery of more suitable materials for EI. Recently, references [16,17] proved that WTe 2 went through an EI transition linked to indirect exciton at around 100 K, in alignment with our expectation.…”
Section: Resultssupporting
confidence: 89%
“…Our approach is based on the previous theoretical work, where it was shown that band-inverted electron-hole bilayers support an unconventional topological phase transition from trivial to the QSH insulator phase via an intermediate insulating phase with spontaneously broken time-reversal symmetry (TRS), arising from the excitonic correlations between the electrons and holes [26]. This exotic TRS broken phase is one of the most prominent candidates for the correlated phases appearing in bandinverted semiconductors due to Coulomb interactions [26][27][28][29][30][31][32][33], and it is consistent with the accumulating experimental evidence of excitonic phenomenology reported in InAs/GaSb quantum wells [34][35][36][37][38] as well as in WTe 2 [39,40]. Moreover, the properties of the TRS broken phase provide a comprehensive explanation [41] of the temperature, voltage and length dependencies of the observed conductance in InAs/GaSb bilayers [7,[42][43][44].…”
Section: Introductionsupporting
confidence: 83%
“…However, the electron-electron interactions are important in these materials if the hybridization of the electron and hole bands is small compared to the exciton binding energy, as can be appreciated by noticing that the bilayer system of spatially separated electrons and holes is the wellknown paradigm system for the realization of an exciton condensate state [9,10]. Indeed, it is now theoretically understood that interactions can lead to a plethora of correlated phases in band-inverted semiconductors [11][12][13][14][15][16][17] and the recent experiments have shown evidence of excitonic phenomenology in InAs/GaSb quantum wells [18][19][20][21][22] as well as in WTe 2 [23,24].…”
Section: Introductionmentioning
confidence: 99%